Economic sanctions against North Korea: The pivotal role of US–China cooperation. (June 2020) - Min, Woo-Jun; Han, Sukhee
At the beginning of 2018, North Korea halted its long-range nuclear- and ballistic-missile development programs and announced that it was willing to denuclearize. Soon afterwards, it reached out to countries including the US, China and South Korea. This sudden change in behavior marked the end of six years of extreme isolation under Kim Jong-un's leadership. To explain why North Korea decided to reach out when it did, the present study examines the 2006–2018 economic sanctions levied on North Korea under the US maximum-pressure policy, carried out partly in cooperation with China. The findings suggest that economic sanctions were ineffective between 2006 and 2016 for two reasons: the lack of cooperation between the US and China, and China's policy of assisting North Korea. In 2006–2016, China and North Korea had shared values and high volumes of trade; there were no clear signs of cooperation between the US and China. However, as trade between China and North Korea began to decrease in late 2017 and early 2018, there were signs of cooperation between the US and China, and changes in North Korean behavior. North Korea came to the negotiating table largely to lift the economic sanctions, which were strengthened by cooperation between the US and China. Increased economic pressure compelled North Korea to normalize its relations with the US, China and South Korea.